Transnasal adenoidectomy in mucopolysaccharidosis. (August 2018) - Harrison, Rebecca; Schaefer, Simone; Warner, Laura; Mercer, Jean; Jones, Simon; Bruce, Iain
Abstract: Background: Mucopolysaccharide (MPS) diseases are a heterogeneous group of inherited, metabolic disorders characterized by accumulation of partially degraded glycosaminoglycans (GAG) in multiple organ systems. Due to accumulation in the airway, patients often present with multilevel airway obstruction and obstructive sleep apnoea (OSA). Adenotonsillar surgery leads to a significant improvement in the severity of OSA in MPS patients. However, access to secure the airway and for conventional surgery can be challenging, due to limited neck extension, macroglossia and reduced mouth opening. This study was undertaken to evaluate the role of transnasal microdebridement and radiofrequent plasma ablation (Coblation) in adenoidectomy to treat OSA in patients with MPS and restricted airway access. Methods: A retrospective case review was performed including patients with MPS undergoing adenoidectomy for OSA in the period between June 2015 and March 2017. In all cases, either a microdebrider (Gyrus Diablo) or a Coblation wand (EVAC70, Smith&Nephew) was used via a transnasal approach guided by nasendoscopy. The primary outcome was effect upon OSA, measured by sleep oximetry and parental report of benefit. The secondary outcomes were surgical complications and risk factors for persistent OSA after surgery. Results: A total of nine patients were identified with a mean age of 9 years (range 3–14 years) at surgery. Post-operative sleep study data was available for eight patients (8/9). Six patients (6/8) had improvement in 4% oxygen desaturation index (ODI-4) with a mean of 8.11 pre-operatively (range 2.69–14.0) and 4.99 postoperatively (range 0.68–8.48). ODI-4 did not improve in two (2/8) patients. Irrespective of sleep oximetry results, improvement in OSA-related symptoms was noted by all parents postoperatively. No risk factors for persistent OSA were identified. Furthermore, no complications were noted in this cohort. Conclusion: Transnasal Coblation and Microdebrider adenoidectomy is a safe and effective surgical treatment for OSA in patients with Mucopolysaccharidosis and adenoidal hypertrophy. As lifespan increases for patients with the Mucopolysaccharidoses, greater emphasis is being given to optimising airway management over the longer-term. This technical note describes the novel application of endoscopic techniques for the management of primary adenoidal hypertrophy when transoral access is restricted, or to debulk recurrent disease that would be challenging to remove via the standard transoral route.